Ravenna and the Traditions of Late Antique and Early Byzantine Craftsmanship Labour, Culture, and the Economy - Cosentino, Salvatore (Millennium-Studien / Millennium Studies, 2020)
Ravenna is the place which preserves the highest number of historical evidence among all centres featuring the late Roman Mediterranean. Its cultural heritage is vast and composite, ranging from papyri to inscriptions, from ivories to marbles. Starting from concrete typologies of hand-manufactured goods existing in the Ravennate milieu, the book aims to explore the multifaceted traditions of late antique and early Byzantine handicraft.